Approach to osteomyelitis treatment with antibiotic loaded PMMA. (January 2017) - Wentao, Zhang; Lei, Guangyu; Liu, Yang; Wang, Wei; Song, Tao; Fan, Jinzhu
Abstract: Background: To reduce the incidence of osteomyelitis infection, local antibiotic impregnated delivery systems are commonly used as a promising and effective approach to deliver high antibiotic concentrations at the infection site. Objective: The objective of this review was to provide a literature review regarding approach to osteomyelitis treatment with antibiotic loaded PMMA. Study design: Literature study regarding osteomyelitis treatment with antibiotic loaded carriers using key terms Antibiotic, osteomyelitis, biodegradable PMMA through published articles. Hands searching of bibliographies of identified articles were also undertaken. Conclusion: We concluded that Antibiotic-impregnated PMMA beads are useful options for the treatment of osteomyelitis for prolonged drug therapy. Highlights: Antibiotic loaded biodegradable PMMA could be used for chronic osteomyelitis. One stage surgery is beneficial after using synthetic polymers. PMMA bone cements remain standard vehicle for antibiotics. Early high elution rate of antibiotics are positive traits for chronic osteomyelitis.